ANALISIS KAPASITAS SALURAN DRAINASE TERHADAP GENANGAN AIR DI KELURAHAN GALONTA KECAMATAN ENREKANG KABUPATEN ENREKANG - Rizal; Jamiluddin Jabir; Inarmiwati Inar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the capacity of drainage channels in mitigating waterlogging in Galonta Village, Enrekang District, Enrekang Regency, and to identify the factors contributing to the occurrence of inundation. The research employed a quantitative approach through hydrological and hydraulic analyses using 10 years (2016–2025) of annual maximum rainfall data collected from the Enrekang, Cendana, and Anggeraja rainfall stations, supported by field observations of the existing drainage system. Hydrological analysis was carried out using the Gumbel Distribution, which was tested using the Chi-Square method. Rainfall intensity was determined using the Mononobe method, the design flood discharge was calculated using the Rational Method, and channel capacity was analyzed using Manning’s Equation. The results showed that the 10-year return period design rainfall was 288.282 mm, with a rainfall intensity of 410.796 mm/hour. The Chi-Square test produced a calculated value of 1.20, which was lower than the critical value of 3.841, indicating that the Gumbel Distribution was suitable for the analysis. The design flood discharge was 0.604 m³/s, while the hydraulic capacity of the drainage channel under ideal conditions reached 0.630 m³/s. However, field observations revealed approximately 0.40 m of sediment accumulation, reducing the effective channel depth, flow area, and channel capacity to approximately 0.261 m³/s. Consequently, the effective channel capacity became lower than the design flood discharge, resulting in a discharge deficit of 0.343 m³/s and causing waterlogging at several locations within the study area. It can therefore be concluded that the primary cause of waterlogging is not the original channel dimensions but sedimentation, channel narrowing, and solid waste accumulation that significantly reduce the effective hydraulic capacity. Regular channel normalization, sediment removal, waste cleaning, and routine maintenance are therefore recommended to improve the performance of the drainage system.